2015
DOI: 10.1016/j.cellimm.2015.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptors regulate innate immune cells and signaling pathways

Abstract: Humans show strong sex differences in immunity to infection and autoimmunity, suggesting sex hormones modulate immune responses. Indeed, receptors for estrogens (ER) regulate cells and pathways in the innate and adaptive immune system, as well as immune cell development. ERs are ligand-dependent transcription factors that mediate long-range chromatin interactions and form complexes at gene regulatory elements, thus promoting epigenetic changes and transcription. ERs also participate in membrane-initiated stero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
627
1
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 770 publications
(657 citation statements)
references
References 86 publications
16
627
1
13
Order By: Relevance
“…Abnormal ER signaling leads to development of a variety of diseases, such as cancer, metabolic and cardiovascular disease, neurodegeneration, inflammation (8), and osteoporosis (3). Chemical binding to the ER is one of the significant mechanisms interfering with process of reproduction (9, 10).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal ER signaling leads to development of a variety of diseases, such as cancer, metabolic and cardiovascular disease, neurodegeneration, inflammation (8), and osteoporosis (3). Chemical binding to the ER is one of the significant mechanisms interfering with process of reproduction (9, 10).…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen effects are mediated through two isoforms of estrogen receptors (ER)-ERα and ERβ. Two isoforms have been identified for the progesterone receptor (PR) as well-PRA and PRB, while androgen receptor has no variants and binds both testosterone and 5α-dihydrotestosterone [5][6][7][8].…”
Section: Sex Hormones and The Immune Systemmentioning
confidence: 99%
“…The study design included the following groups: 1) pregnant women (n=96) who were in their second trimester (weeks [16][17][18][19][20][21][22][23][24] or third trimester (weeks 25-34), 2) postpartum women (n=96) who were evaluated 6 months after delivery.…”
Section: Study Populationmentioning
confidence: 99%
“…They are able to modulate the activities of all the cells involved in the immune inflammatory response depending on their concentration. 16,17 Studies suggested that progesterone and estrogen have both immune-stimulatory and immune-suppressive effects depending on the concentration. Table 1.…”
mentioning
confidence: 99%